Enhancement of Academic Research Activity in HEIs with the Usage of Foresight Methodology - Schmeleva, Anna Nikolaevna; Umnova, Maria Gennadyevna (International Review of Management and Marketing, 2017)
Applicability of this paper is determined by a number of factors: fragmentary nature of the topic of foresight in HEIs, often weak connection between research projects in various departments and divisions in universities, insufficient degree of commercialization of academic research projects, lack of foundation for formulation of academic priority subject fields. Foresight methodology makes it possible to gather data necessary for making decisions on current state and directions of research; keep track of projects that are of interest to government bodies and business structures, as well as determine necessary resources for allocation in order to achieve leading positions. With this in mind, it is possible for a HEI to formulate scenarios and execution stages of ‘Foresight’ program and define offer-projects for funding from both state-financed and off-budget sources. The intended effect from foresight program implementation is to assure significant increase in revenue side of academic research projects. Thus, this paper focuses on establishing the connection between formulation of academic research policy and the end results of foresight usage in a specific subject area. Keywords: foresight methodology, academic research, development JEL Classification: O21